IMPLEMENTASI MANAJEMEN MUTU TERPADU (STUDI TRANSFORMATIF PADA PERGURUAN TINGGI) - Buyung Syukron (LP2M IAIN kUDUS, 2016)
AbstractThe system of quality management implemented with the consistent commitment would provide the benefits and success for all stakeholders in the University. To obtain those benefits and success should be based on several principles of the established quality management. The starting entry of foreign University enliven the “competition” existed in Indonesia. The University is not only seen as the center of science, research, and community service, but also as the corporation entity of “producing science” that needs to compete to ensure the survival. The competition, as experienced by companies for profit, covers the competition of quality, price, and service. University as nonprofit entity also faces the same case. To manage these all, it needs the knowledge and skill of management namely integrated quality management of University. Keywords: Integrated Quality Management, Transformation of Management, University